2016
DOI: 10.3892/mco.2016.821
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of weekly paclitaxel treatment as a single agent chemotherapy following first-line cisplatin treatment in urothelial bladder cancer

Abstract: Abstract. The aim of the present study was to investigate the efficacy of paclitaxel following a first-line cisplatin regimen in patients with metastatic bladder cancer. The present study retrospectively evaluated the clinical effects and toxicities of second-line paclitaxel regimens following first-line cisplatin treatment in metastatic bladder cancer. A total of 42 patients with progressing metastatic urothelial bladder cancer following cisplatin-based chemotherapy were enrolled. The patients received weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…Taxanes have been shown to be active as treatment options for urothelial bladder cancer. [115][116][117][118] Based on these results, several groups are exploring 2-and 3-drug combinations using these agents, with and without cisplatin. A randomized phase III trial was conducted to compare GC and GC plus paclitaxel in 626 patients with locally advanced or metastatic urothelial cancer.…”
Section: Chemotherapy For Metastatic Diseasementioning
confidence: 99%
“…Taxanes have been shown to be active as treatment options for urothelial bladder cancer. [115][116][117][118] Based on these results, several groups are exploring 2-and 3-drug combinations using these agents, with and without cisplatin. A randomized phase III trial was conducted to compare GC and GC plus paclitaxel in 626 patients with locally advanced or metastatic urothelial cancer.…”
Section: Chemotherapy For Metastatic Diseasementioning
confidence: 99%
“…Combination chemotherapy has been shown to reduce the recurrence rate of BUC and to improve patients' survival (4). Treatment with the microtubule stabilizing agent, paclitaxel has also proven to be an effective therapy against BUC (5,6). Recent phase III clinical trials have found that a PCG (paclitaxel plus cisplatin plus gemcitabine) regimen, consisting of the addition of paclitaxel to a standard chemotherapy regimen of cisplatin plus gemcitabine (GC), can improve the overall response rate and overall survival rate of patients with BUC (7).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, as stated in the introduction, there are currently no established second-line chemotherapy regimens for cisplatin-resistant UC. However, there are several reports that paclitaxel-based chemotherapy has had some effectiveness in terms of improvement of quality of life and prognosis in patients with cisplatin-resistant UC (18,23). In recent years, immune-checkpoint inhibitors have been reported as a novel treatment modality for patients with advanced UC, including platinum-treated advanced UC (21,22).…”
Section: Discussionmentioning
confidence: 99%